Ethanol-Water Separation by Pressure Swing Adsorption (PSA) - A. Abdel-Rahman, Zaid; M. Mahmood, Abdulrahman; J. Ali, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Single long spiral tube column pressure swing adsorption (PSA) unit, 25 mm diameter, and 6 m length was constructed to study the separation of water from ethanol at azeotropic concentration of 95 wt%. The first three meters of the column length acted as a vaporizer and the remaining length acted as an adsorber filled by commercial 3A zeolite. The effect of pressure, temperature and feed flow rate on the product ethanol purity, process recovery and productivity were studied. The results showed that ethanol purity increased with temperature and pressure and decreased with feed flow rate. The purity decreased with increasing productivity. The purity range was 98.9 % to 99.6 %, the recovery range was 0.82 to 0.92 and the productivity range was 0.3 to 1.05 kg ethanol/kg zeolite.h.